or

ask mattrab Visit www.askmattrab.com for more academic resources.

HCF and LCM

Hcf

H.C.F 

Q. Find H.C.F : x3-1,  x4+x2+1, and    x3+2x2+ 2x +1 

Soln: 

1st exp:   x3- 1

              = (x -1) (x2 + x +1) 

2nd exp:   x4+x2+1 

              =( x2)2 + 12 + x2  

              = (x2+ 1)2 -  2.x2.1 + x2 

              = (x2+ 1)2 - x2 

              = ( x2 +1 +x) (x2+1 - x) 

             = ( x2+ x +1) (x2- x + 1) 

3rd exp:   x3+ 2x2+ 2x +1 

              = x3+1+ 2x2+ 2x 

              = (x+1)( x2- x + 1)+ 2x (x+1) 

              = (x+1) (x2 - x + 1+ 2x)

              = (x+1) (x2 + x + 1) 


Therefore, H.C.F.= (x2 + x + 1)